The postpartum period Case Study on Postpartum Mothers with Milk Duct Obstruction at the Health Facility in Padurungan, Work Area of Tanah Merah Community Health Center, Bangkalan - Pratiwi, Dyah Febri Putri (LPPM Universitas dr. Soebandi, 2024)
The postpartum period is a process after the release of placenta until the reproductive organs return to the same way as before pregnancy. The postpartum period is closely related to the breastfeeding process, the breastfeeding process is a long process that must be known and prepared by postpartum mothers related to breast care, nipple conditions, breastfeeding techniques and breastfeeding patterns. If this not prepared since pregnancy, problems can occur during the postpartum period, one of which is the breast milk dam. Breast milk dams if left untreated can lead to ongoing complications. The purpose of this case study is to find out the risk factors and management of breast milk dams that have been carried out by health workers in health facilities in the working area of the Tanah Merah Bangkalan Health Center. This case study uses the multiple case design method, conducted from January to May 2024. The subjects in this case study are postpartum mothers with the first delivery, a total of 2 people, postpartum on days 3-7. Data collection was carried out by interviews using questionnaire and observation instruments to obtain general data from case studies. Data analysis using tables and narration. The results of the case study showed that the main cause of breast milk dams in subject 1 was breastfeeding techniques, while in subject 2 was breast care and good and correct breastfeeding techniques. The management obtained by subject 1 is breastfeeding techniques, while subject 2 is breast care and breastfeeding techniques. To prevent the occurrence of breast milk dams, it is hoped that there will be health education about problems that occur in postpartum mothers, especially breast milk dams which include breast care, identification of milk nipples since pregnancy and good and correct breastfeeding techniques so that breast milk dam problems do not occur.